Edmodo Engaging and Studentsâ Motivation Toward Studentsâ Writing Ability - Setiawati, Setiawati; Deswarni, Dini (Proceedings of the UR International Conference on Educational Sciences, 2018)
This study aimed to investigate the influenceof Edmodo Engaging and Studentsâ Motivation Toward Studentsâ Writing Ability at English Department of STAI Hubbulwathan Duri. It was a correlational research design. Then, it also involved 13 students as a sample. Three hypotheses were posed in this study firstly to find out the influence of Edmodo toward studentsâ writing ability. Secondly, studentsâ motivation toward studentsâ writing ability. The last Edmodo engaging and studentsâ motivation toward studentsâ writing ability. The research findings showed that there was an influence of Edmodo engaging and studentsâ motivation toward studentsâwriting ability of English Department of STAI Hubbulwathan Duri in academic year 2017/2018. This study used SPSS to analyze the data. The data were correlated by using Pearson Product Moment Correlation (SPSS). Then, the level significance 5% = 0.05 because this study used oral test and Significant F change = 0.024. The degree of correlation between Edmodo and studentsâ motivation toward studentsâ writing ability is 0.726. Category between 0.5 â¤ r <0.726 is strong. So, based on coefficient correlation (r) value from the formula, 0.726 is strong. It showed that the hypothesis alternative (Ha3) was accepted. In conclusion, Edmodo Engaging and studentsâ motivation had a strong contribution to studentsâ writing ability.